Propuesta de intervención del espacio público en la ciudad construida: Caso de estudio Barrio La Dolorosa entre avenida Leopoldo Freire y avenida Eloy Alfaro - Panchi Esparza, Marlon Fabricio (2023)
This project focuses on the urban-architectural intervention in the existing public spaces in the Barrio de La Dolorosa, EPAD 1 ( Inter- parroquial Ter- minal- Plaza Abdon Calderón), and EPAD 2 with its main streets and ave- nues, seeking to provide a solution to the vehicular and pedestrian chaos, which occurs in the area, due to the inter-parish terminal located within Plaza Abdon Calderón and the disorganization of both commercial, cultu- ral, and recreational activities, which are part of the identity of Barrio La Dolorosa, in addition to concentrating different equipment and commercial premises therefore, they require public spaces as meeting and recreation places, based on a diagnostic analysis at the macro and micro level, the main flows of urban mobility are identified, reducing the vehicular importance but preserving its strategic location as an articulator between income South of Riobamba with its Urban Center, as well as the strategies as they are the synthesis of research and that promote activities within public spaces